Identification of Children with Learning Barriers (Dysgraphia) and Treatment in Elementary School - Muhammad Fakhri Saifudin; Yustri Mindaryani; Susi Lestari; Minsih Minsih; Choiriyah Widyastuti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Background: Education in elementary schools certainly has the aim of properly realizing the function of national education. However, without realizing it, in carrying out national functions certain obstacles come from both students and teachers. One of the obstacles that is often encountered is dysgraphia. Where dysgraphia is a difficulty experienced by children in reading due to poor writing and spelling in children. Therefore, researchers in this study have the aim of identifying learning barriers and handling them in one of the elementary schools in Sukoharjo Regency. This research uses a qualitative approach. The research participants were guidance and counseling teachers, class teachers, and students. Data collection techniques include observation, interviews, and, documentation. The analysis technique used is interactive data analysis through data reduction, data presentation, and data conclusions. The results of the research show that children with learning disabilities have types of dyslexia dysgraphia, motor dysgraphia, and spatial dysgraphia. Therefore, children with this type of digraphia obstacle can be overcome by using strategies used by class teachers and guidance and counseling teachers in various ways, namely by providing motivation to students, providing interesting media, writing pre-school activities, tracing letters, writing block letters and practicing in writing cursive letters.